TARI TAN BENTAN DI KANAGARIAN SANIANG BAKA KABUPATEN SOLOK - Meirita Hardina Sari; Nerosti Nerosti; Darmawati Darmawati (FBS Universitas Negeri Padang, 2018)
Abstract This article aimed to describe the form of Tan Bentan Dance in the community of Kanagarian Saniang Baka in Solok Regency. The object of this research was Tan Bentan Dance at Kanagarian Saniang Baka Solok Regency. The techniques of data collefction were conducted by literature study, observation and interviews. Then, there were several steps in analyzing the data, they were grouping data, analyzing data, describing data and making reports. The results of the study showed that Tan Bentan dance was one of the arts and cultures that were still developing in Kanagarian Saniang Baka, Solok Regency. There had been no change in the motion of Tan Bentan Dance from the past to the present and there were many repetitions in each stage. Previously, Puti Bungsu figure was played by men, and now the role of Puti Bungsu was played by women. The floor patterns of Tan Bentan Dance were circles as well as on Randai. Meanwhile, in the third and fifth round there was a slight change in floor pattern. The most floor pattern of Tan Bentan dance was circular. The number of Tan Bentan dancers was three people and one musician, with the characters of Cindua Mato, Lembang Jayo and Puti Bungsu. However, it could be seen from Tan Bentan's Dance that was performed at Marzuki Ismail Park Jakarta that the Puti Bungsu figure was played by male dancer and female dancer that had the creation of dance performances. Keywords: Tan Bentan Dance